2018
DOI: 10.1038/s42003-018-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Pinopsin evolved as the ancestral dim-light visual opsin in vertebrates

Abstract: Pinopsin is the opsin most closely related to vertebrate visual pigments on the phylogenetic tree. This opsin has been discovered among many vertebrates, except mammals and teleosts, and was thought to exclusively function in their brain for extraocular photoreception. Here, we show the possibility that pinopsin also contributes to scotopic vision in some vertebrate species. Pinopsin is distributed in the retina of non-teleost fishes and frogs, especially in their rod photoreceptor cells, in addition to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Consistent with this idea, there has been a very recent report [72] that pinopsin evolved as the ancestral dim-light visual opsin, with a lower rate of thermal activation than cone opsins. Accordingly, it would seem likely that the ancestral low-light photoreceptor that we proposed above would have expressed pinopsin as its visual pigment.…”
Section: The Origin Of Specialization For Operation At High and Low Intensitiesmentioning
confidence: 74%
“…Consistent with this idea, there has been a very recent report [72] that pinopsin evolved as the ancestral dim-light visual opsin, with a lower rate of thermal activation than cone opsins. Accordingly, it would seem likely that the ancestral low-light photoreceptor that we proposed above would have expressed pinopsin as its visual pigment.…”
Section: The Origin Of Specialization For Operation At High and Low Intensitiesmentioning
confidence: 74%
“…S4). This suggests the possibility that the common ancestor of the gnathostomes had already acquired the pinopsin gene for pineal photoreception and that the gene was lost from the teleost lineage 19 . Moreover, pinopsin shares common molecular properties with rhodopsin, that is, pinopsin photo-converts to meta II, whose λ max lies in the UV region, to couple with Gt 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The full-length ORF sequences of spotted gar Rh1-1 (Exorh) (XM_006630940), Rh1-2 (XM_006630625) and pinopsin (XM_015367820) and the partial ORF sequence of coral catshark pinopsin (LC328553) were isolated by PCR from the 1st strand cDNA from eyes as shown in our previous study 19 . The full-length cDNA of Siberian sturgeon pinopsin (LC365918) and the partial ORF sequence of gray bichir pinopsin (LC328554) were isolated by PCR from the 1st strand cDNA from brain.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be stressed that the pineal organ of 4-week-old turkeys comprises extremely well-developed rudimentary photoreceptor pinealocytes with the apical protrusions containing pinopsin [ 33 ]. Moreover, recent studies suggested that pinopsin is responsible for highly sensitive light reception in the retinas of lower vertebrates, which points to its ability to detect low-intensity light [ 43 ]. Regarding the second option, the retinal photoreceptor cells are good candidates because they are color selective and highly light sensitive.…”
Section: Discussionmentioning
confidence: 99%